2012
DOI: 10.4236/ss.2012.39087
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life after Treatment of Abdominal Aortic Aneurysm with Open and Endovascular Techniques—A Two-Year Follow Up

Abstract: Background: Patients with Abdominal Aortic Aneurysm can be treated with two different surgical methods: Open Repair (OR) or Endovascular Aortic Repair (EVAR). These two different treatments can probably result in different sense of Health Related Quality of Life, both in a short term and a long term perspective. The purpose of this prospective study was to examine patients' Health Related Quality of Life after surgical treatment of Abdominal Aortic Aneurysm over two years using different instruments for the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this context, the literature is inconclusive because some centers have reported a short LOS and even an outpatient procedure in selected EVAR patients 11,12 in contrast to other reports of LOS of more than 4 days. 4,5,9,13,14 Several trials have demonstrated a reduction in the inflammatory response, postoperative nausea and vomiting, and pain by administration of preoperative glucocorticoids. [15][16][17][18][19] Although glucocorticoids have been used in EVAR, 11,20 this approach has not been tested in a randomized setting.…”
mentioning
confidence: 99%
“…In this context, the literature is inconclusive because some centers have reported a short LOS and even an outpatient procedure in selected EVAR patients 11,12 in contrast to other reports of LOS of more than 4 days. 4,5,9,13,14 Several trials have demonstrated a reduction in the inflammatory response, postoperative nausea and vomiting, and pain by administration of preoperative glucocorticoids. [15][16][17][18][19] Although glucocorticoids have been used in EVAR, 11,20 this approach has not been tested in a randomized setting.…”
mentioning
confidence: 99%
“…Evaluating and measuring recovery following IC is complicated as many factors may influence the patients’ own opinions about their recovery. In post-surgical and ICU follow ups, HRQL has been used in order to measure patients’ opinions on their quality of life [ 12 , 13 ]. For the recovery instruments that are used, most have focused simply on physical symptoms and mental issues, omitting many other facets of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the questionnaire was developed upon the understanding that recovery is seen as a process of regaining health, a movement towards integration even if setbacks sometimes occur. Therefore, dimensions that also reflect existential, social and spiritual life issues were seen as important as previous studies have stated these aspects impact patients’ recoveries [ 11 13 , 20 , 32 ]. For example, patients expressed that they felt well but, at the same time, were in need of help from family members [ 20 ] or suffered from thoughts of death and could not look forward to anything in life [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations